Economic diplomacy essays and reflections by Singapore's negotiators - Lim, C. L.; Liang, Margaret. (World Scientific Pub. Co., 2011)
Singapore, a small Southeast Asian country with limited resources, transformed itself from a trading post to a successful, cosmopolitan nation with one of the most impressive growth rates in the world. Less well known, however, has been its role in regional and global trade negotiations. This book is a collection of sixteen essays written by a group of diplomats, policy-makers, and professors who became involved in international economic affairs, notably in GATT/WTO, regional and bilateral free trade negotiations. Here, they reveal their thoughts about the world economy and trading system, reflect on their experiences, and explain how they promoted national interests while advancing the global trade agenda. This book will appeal not only to professional diplomats, but to anyone interested in how international economic diplomacy works and Singapore's role and perspective as an open trading nation.